1996
DOI: 10.3109/00365529609010360
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplastic Polyposis of the Large Bowel Three Cases and a Review of the Literature

Abstract: Small hyperplastic polyps of the large bowel constitute a frequent non-neoplastic lesion, whereas large or multiple hyperplastic polyps are rare. Here we report three cases of multiple small polyps together with some large hyperplastic ones. Two of the cases had a primary carcinoma in the bowel before onset of the polyps. The neoplastic potential of the hyperplastic polyp is discussed on the basis of the most recent investigations and the three presented cases. The hyperplastic polyp does not seem to be direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…3 Although most of the polyps in this case were hyperplastic in nature, one showed serrated adenomatous change, typified by a serrated architecture, with cells showing abundant eosinophilic cytoplasm, goblet cell depletion, and oval vesicular nuclei with prominent nucleoli and nuclear stratification ( Figure 2B). No areas of moderate or severe dysplasia were seen in this lesion, and no adenomatous polyps of the usual type were seen within the colectomy specimen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Although most of the polyps in this case were hyperplastic in nature, one showed serrated adenomatous change, typified by a serrated architecture, with cells showing abundant eosinophilic cytoplasm, goblet cell depletion, and oval vesicular nuclei with prominent nucleoli and nuclear stratification ( Figure 2B). No areas of moderate or severe dysplasia were seen in this lesion, and no adenomatous polyps of the usual type were seen within the colectomy specimen.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the formation of an adenoma, with its disordered crypt architecture, allows the exposure of proliferating cells to fecal carcinogens. 3 This leads in some cases to p53 mutations and subsequent neoplastic progression via impaired apoptosis and chromosomal instability. It is plausible that a similar mechanism may be at work in the hyperplastic polyp/serrated adenoma lesions typical of the hyperplastic polyposis syndrome.…”
Section: Mutation Of P53 Is An Early Event In Malignant Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…They frequently arise at the crest of a mucosal fold where they present as small, sessile polyps usually measuring less than 5 mm in diameter with a smooth convex surface 1. Although traditionally regarded as non-neoplastic, recent evidence has shown hyperplastic polyps to have molecular features of neoplasia 2…”
Section: Discussionmentioning
confidence: 99%
“…These criteria were recently redefined and this condition is currently referred to as serrated polyposis syndrome (SPS). A number of patients have been reported as having CRC and concurrent SPS (10)(11)(12)(13)(14)(15)(16), suggesting that SPS may be an alternative pathway for the development of CRC. However, SPS has not yet been extensively investigated in Japan and its clinical characteristics, causes and association of SPS to CRC have not been adequately evaluated.…”
Section: Introductionmentioning
confidence: 99%